A global phylogenetic analysis of Japanese tonsil-derived Epstein–Barr virus strains using viral whole-genome cloning and long-read sequencing. (12th March 2021) - Yajima, Misako; Kakuta, Risako; Saito, Yutaro; Kitaya, Shiori; Toyoda, Atsushi; Ikuta, Kazufumi; Yasuda, Jun; Ohta, Nobuo; Kanda, Teru
Abstract : Epstein–Barr virus (EBV) establishes lifelong latent infection in the majority of healthy individuals, while it is a causative agent for various diseases, including some malignancies. Recent high-throughput sequencing results indicate that there are substantial levels of viral genome heterogeneity among different EBV strains. However, the extent of EBV strain variation among asymptomatically infected individuals remains elusive. Here, we present a streamlined experimental strategy to clone and sequence EBV genomes derived from human tonsillar tissues, which are the reservoirs of asymptomatic EBV infection. Complete EBV genome sequences, including those of repetitive regions, were determined for seven tonsil-derived EBV strains. Phylogenetic analyses based on the whole viral genome sequences of worldwide non-tumour-derived EBV strains revealed that Asian EBV strains could be divided into several distinct subgroups. EBV strains derived from nasopharyngeal carcinoma-endemic areas constitute different subgroups from a subgroup of EBV strains from non-endemic areas, including Japan. The results could be consistent with biased regional distribution of EBV-associated diseases depending on the different EBV strains colonizing different regions in Asian countries.